Impact of the Capital Adequacy Ratio (CAR) and Mudharabah on the Return on Asset (ROA) on Sharia General Banks Registered in the Financial Services Authority (OJK) - Sapitri, Niluh Anik; Irawan, Besse Khadijah (Indonesian Journal Publisher, 2023)
The objective of this study was threefold: (1) to assess the impact of the capital adequacy ratio on the return on assets of Islamic Commercial Banks that are registered with the Financial Services Authority (OJK), (2) to examine the influence of mudharabah return on assets at Islamic Commercial Banks registered with OJK, and (3) to ascertain the combined effect of the capital adequacy ratio and mudharabah return on assets at Islamic Commercial Banks registered with OJK. The investigation was carried out throughout the period spanning from July to August of 2021. The research undertaken employed a quantitative-descriptive methodology, utilizing an associative approach. The utilized data source consisted of secondary data. The population under consideration encompasses the complete set of financial statements belonging to Islamic Commercial Banks (ICB) in Indonesia that were registered with the Otoritas Jasa Keuangan (OJK) throughout the period spanning from 2016 to 2020. The employed sample approach was the saturation sampling technique. The data was acquired from a collection of financial records comprising a total of 60 samples. The approaches employed for data collection involved the utilization of observation and documentation methods. The employed methodology for data analysis was multiple linear regression. The findings of this study suggest that there is a positive and statistically significant relationship between the capital adequacy ratio and return on assets at Islamic Commercial Banks, albeit to a partial extent. (2) The impact of mudharabah on the return on assets of Islamic Commercial Banks was found to be insignificant. (3) However, when considering the capital adequacy ratio and mudharabah together, a positive and substantial relationship was observed with the return on assets of Islamic Commercial Banks. The findings of the aforementioned study indicate that the capital adequacy ratio and mudharabah significantly impact the return on assets of Islamic Commercial Banks that are registered with the Otoritas Jasa Keuangan (OJK). Hence, the bank possesses the ability to oversee and uphold the standard of the capital adequacy ratio and mudharabah on return on assets (ROA) in order to enhance the bank's profitability. The findings suggest that both the capital adequacy ratio and mudharabah exhibit a favorable influence on the return on assets, as they demonstrate a positive impact and the ability to enhance bank profitability.